Project for the 1992 Chicago World's Fair - Stuart Cohen; Anders Nereim (Oz, 1984)
In 1992 Chicago will be the site of a centennial celebration of America's discovery. As in 1892, Chicago will host a "World's Columbian Exposition" dedicated to the theme of discovery…